TANGGAP COVID – 19 MASYARAKAT DI RT TENGKAN KELUARAHAN MAKALE KABUPATEN TANA TORAJA TAHUN 2020 - Dewi Purnama Windasari; Riswan Hilal (LPPM STIK Makassar, 2021)
Corona virus Disease-2019 (COVID-19) is known to cause respiratory tract infections in humans ranging from colds to more serious coughs such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). The spread of the COVID-19 virus is increasing faster through droplets of saliva or out of the nose when an infected person coughs or sneezes.(Prasetyo and Suherlan 2020) However, there is still very little community in RT Tengkan, Lamunan Village, Makale District, Tana Toraja implementing health protocols to avoid the spread of the corona virus. Therefore, there is a need for an understanding of the health protocol for handling COVID-19. Based on these problems, the authors carry out community service through the STIK Makassar Response COVID-19 Real Work Lecture (KKN) activities carried out using methods of supporting public safety against COVID-19. Such as making banners about health protocols, building hand washing stations, distributing masks to break the chain of distribution of viurs, and working together to clean up the environment by applying physical distancing. Hopefully with this program the community can comply with health protocols. As a result of this activity, I managed to distribute 20 masks to people who often leave their homes, put up health protocol banners around people's homes, build hand washing stations around Lamunan Village, and invite people to work together to clean the road to the Zion church by implementing health protocols.